Analysis of a Tall Structure Considering Composite Steel Section Columns using ETAB - Jain, Parag; Satbhaiya, Rahul (International Journal of Scientific Research in Civil Engineering, 2019)
The present work carried out to analyze the structural performance of high rise building structure constructed using composite columns in combination with RCC beam & Slab. In this study a model of stilt +10 storied framed structure subjected to seismic loading of Zone – II analyzed using equivalent static method as per IS 1893-2002 on software package ETABS. Two similar models were prepared with different type of columns – RCC Column and CFST Column and similar loading conditions were applied to them. Those two models were analyzed and result obtained were compared in terms of structural performance on following parameters – Maximum story displacement, Story shear, story drift, story overturning moment and section size reduction.
Keywords: Composite Structure; Analysis, Seismic; ETAB; Tall Structure; Rigidity; Sectional Design